Spectrum of biopsied oral and maxillofacial lesions in a tertiary care hospital of Karachi, Pakistan - Raza, Syeda Hala; Ahmed, Sufyan; Zafar, Maryam (Journal of Fatima Jinnah Medical University, 2021)
Objectives: The burden of benign and malignant maxillofacial lesions in developing countries has increased rapidly over the years. Objective of this study was to provide a spectrum of oral and maxillofacial lesions biopsied in a tertiary care hospital of Karachi, Pakistan and to contribute in baseline data of target population. Patients and methods: This descriptive cross sectional study was made of biopsies performed in patients presenting to OPD of Oral and Maxillofacial Surgery Department, Abbasi Shaheed Hospital Karachi, Pakistan, between July 2018 till June 2020. A total of 652 patients belonging to either gender, 18-75 years of age, incisional or excisional biopsy were included. Recurrent or previously diagnosed lesions and patients not willing to give informed consent were excluded. Data including age, gender, site and histopathological diagnosis was recorded on a performa. Descriptive statistical analysis was done using SPSS version 26. Result: Out of 652 biopsies performed, (82.9%, n=541) belonged to soft tissues and (17.1%, n=111) were hard tissue lesions. The mean age of patients was 41.82 years, with a male to female ratio of 2.9:1. The most frequent sites biopsied were buccal mucosa (50.9%, n=332) and posterior mandible (10.6%, n=69). Oral squamous cell carcinoma (OSCC) (55.1%, n=359) was the most commonly reported soft tissue lesion with major involved sites buccal mucosa (74.4%, n=267), dentoalveolar mucosa (8%, n=29) and lateral border of tongue (7.2%, n=26) and for hard tissue the most common lesion was ameloblastoma of posterior mandible (3.5%, n=23). Conclusion: This study provides useful information about distribution of oral and maxillofacial lesions and highlights OSCC as the single most frequent diagnosis involving a much younger male population.